PENGARUH PENERAPAN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS VII SMP NEGERI 26 MEDAN - Agnes Sitanggang; Surya Dharma; Sri Hadiningrum; Oksari Sihaloho; Fazli Rachman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of differentiated learning on student learning outcomes in Pancasila Education in grade VII at SMP Negeri 26 Medan. This study was conducted based on the low learning outcomes of students, as indicated by the large number of students who did not meet the minimum passing grade (KKM), as well as the learning process that was still dominated by conventional methods without considering differences in learning styles, interests, and readiness of students. This study used a quasi-experimental method with a Pre-test-Post-test Control Group Design, involving 64 students consisting of class VII-E as the experimental class and class VII-H as the control class. The experimental class was given treatment in the form of differentiated learning that accommodated the readiness, interests, and learning profiles of students, while the control class was taught using conventional learning. The research instrument was a learning outcome test administered before and after the treatment. The data were analyzed using normality, homogeneity, Paired Sample T-Test, and Independent Sample T-Test tests with the help of the SPSS 25 program. The results showed a significant increase in the learning outcomes of the experimental class, with the average score increasing from 70.72 to 84.91 after the implementation of differentiated learning. Meanwhile, the control class only experienced a small increase from 69.38 to 70.03, or 0.65 points. The Paired Sample T-Test results showed Sig. (2-tailed) = 0.000 < 0.05, indicating a significant difference between the pretest and posttest scores in the experimental class. The Independent Sample T-Test also produced a Sig. value of 0.000 < 0.05, with a posttest average difference of 14.88 points between the two classes, proving that differentiated learning has a significant effect on student learning outcomes. It can be concluded that the application of differentiated learning is ffective in improving Pancasila Education learning outcomes while creating an adaptive and student-centered learning process.